Internet Eavesdropping: Information Security Challenge in the Cyberspace - Rudy Agus Gemilang Gultom (The Republic of Indonesia Defense University, 2017)
In the era of information globalization the activity of information tapping over the Internet is one of the negative impacts of the interconnectivity between the Internet users and the ease of the process of exchanging data on the Internet. The disclosure of classified sensitive or confidential information or the loss of important documents is the result of information that is not well protected. Therefore, Internet users need to know more information about eavesdropping via the Internet to improve information security.